The little monk and other stories - Dāsa, Gaurahari (Rupa, 2011)
The little monk -- The sin -- Father -- The illusive tree -- The glass puppet -- The house -- Urmila -- A piece of gold -- Settling scores -- The chakunda tree -- The nail -- Ahalya's wedding -- Crime and punishment -- Where shall I go?